Study on Vegetative Propagation of Maiden-hair Tree (Ginkgo biloba, Linn.) in Haryana State of India - an Extant Curious Gymnosperm of China - Ramesh Singh, D. R. (Indian Forester, 2007)
’Maiden-hair tree’, Ginkgo biloba, Linn. is an extant gymnosperm that was discovered in China after fossils of similar plants were discovered earlier. In India planting efforts are meager as it is a costly plant and requires near temperate conditions for its survival. It is a dioecious plant species, i.e., with separate male and female plants. Seed production in female plants growing along male plants occurs after about 20 years. Seeds are malodorous, thus elite male plants that grow fast are being selectively raised by induction of adventitious roots in stem cuttings using 8,000 ppm of IBA in USA where it is being planted along avenues as the tree is large, sturdy and long lived. Efforts to multiply this plant by stem cuttings to over come short supply of costly seedlings was undertaken in three nurseries of Haryana State using Plant Growth Regulators (PGRs), viz., IBA, NAA, Catechol and Putrescine and 50% rooting response was observed in PGR treated cuttings.